Violence in the Big Apple throughout the COVID-19 pandemic: A borough-specific analysis. (July 2022) - Wolff, Kevin T.; Intravia, Jonathan; Baglivio, Michael T.; Piquero, Alex R.
Abstract: In early 2020, the world faced a rapid, life-changing, public health crisis in the form of the Coronavirus (COVID-19) pandemic. The pandemic and its associated social-distancing measures collided with a period of social unrest following the murder of George Floyd at the hands of Minneapolis police and persisted for nearly two years following its emergence. The current study adds to existing research by examining the effect of these events on the incidence of violence (shootings and assaults) in New York City (NYC) over a longer period of time, both in the city as a whole and at the borough-level. To accomplish this, the current study draws from publicly available data using series of analytical techniques to account for underlying trends, seasonality, and temperature while also estimating borough-specific effects. Results indicate that the prevalence of COVID-19 cases, associated social-distancing mandates, and the period of social unrest following Floyd's murder were associated with violence in NYC. Further, findings suggest while a number of the factors explored had consistent effects across each of NYC's five boroughs there was some evidence of heterogeneity. The implications for future research on the COVID-19 pandemic are discussed. Highlights: We assess the association of pandemic lockdown orders and unrest following George Floyd's murder with assaults and shootings. NYC borough-specific effects are examined, controlling for positive COVID cases, daily arrest counts, and daily temperature. Positive COVID-19 cases were negatively associated with both shooting and assault incidents across boroughs. Following Floyd's murder increased shootings occurred in four boroughs, with Staten Island evidencing decreased shootings. Borough differences demonstrate trends in violence in some areas is at times contradictory to the overall citywide trends.